2012
DOI: 10.1177/1012690212455961
|View full text |Cite
|
Sign up to set email alerts
|

Creating or awakening national pride through sporting success: A longitudinal study on macro effects in the Netherlands

Abstract: Like many other countries, the Dutch government increased investments in elite sports in the last decennium, partly driven by the ambition to organise the Olympic Games in 2028 in the Netherlands. One of the most important legitimations for this ambition is that elite sports events and national achievements should foster national pride, social cohesion and international prestige.In this article we present and discuss the results of a study on the relationship between Dutch international sport achievements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 21 publications
9
74
0
4
Order By: Relevance
“…Some scholars have argued that increased levels of well-being and pride that result from sporting success do not last for long and start to vanish shortly after a sport event is over (Elling et al 2014;Pfitzner and Koenigstorfer 2016). The data presented here buttresses this notion and, at the same time, reject the assumption of persistency (H#3).…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Some scholars have argued that increased levels of well-being and pride that result from sporting success do not last for long and start to vanish shortly after a sport event is over (Elling et al 2014;Pfitzner and Koenigstorfer 2016). The data presented here buttresses this notion and, at the same time, reject the assumption of persistency (H#3).…”
Section: Discussionsupporting
confidence: 53%
“…In a German study, it was reported that two thirds of the Germans agree with the statement 'I am happy if German athletes win many medals at Olympic Games or World Championships' (Hallmann et al 2013). A Dutch study points to a small, short-term increase in SWB during the 2010 FIFA World Cup, where a surprisingly strong Dutch national team advanced to the tournament's final (Elling et al 2014). However, other major sport events (e.g.…”
Section: Hosting Major Sporting Events and Well-beingmentioning
confidence: 99%
See 3 more Smart Citations